Correction: Partially embedded gold nanoislands in a glass substrate for SERS applications. Issue 3 (4th December 2014) - Yaseen, Mohammad Tariq; Chen, Minfeng; Chang, Yia-Chung
Abstract : Correction for 'Partially embedded gold nanoislands in a glass substrate for SERS applications' by Mohammad Tariq Yaseen et al., RSC Adv., 2014, 4, 55247–55251.